ACE2 utilization of HKU25 clade MERS-related coronaviruses with broad geographic distribution - Chen Liu; Young‐Jun Park; Chengbao Ma; C Stuart; Risako Gen; Yucheng Sun; Xiao Yang; M C Lin; Qing Xiong; Jun-Yu Si; Peng Liu; David Veesler; et al. (2025)
Abstract Dipeptidyl peptidase-4 (DPP4) is a well-established receptor for several MERS-related coronaviruses (MERSr-CoVs) isolated from humans, camels, pangolins, and bats (1–6). However, the receptor usage of many genetically diverse bat MERSr-CoVs with broad geographical distributions remains poorly understood. Recent studies have identified angiotensin-converting enzyme 2 (ACE2) as an entry receptor for multiple merbecovirus clades. Here, using viral antigen and pseudovirus-based functional assays, we demonstrate that several bat merbecoviruses from the HKU25 clade previously thought to utilize DPP4 (7), employ ACE2 as their functional receptor. Cryo-electron microscopy analysis revealed that HsItaly2011 and VsCoV-a7 recognize ACE2 with a binding mode sharing similarity with that of HKU5 but involving remodeled interfaces and distinct ortholog selectivity, suggesting a common evolutionary origin of ACE2 utilization for these two clades of viruses. EjCoV-3, a strain closely related to the DPP4-using MERSr-CoV BtCoV-422, exhibited relatively broad ACE2 ortholog tropism and could utilize human ACE2 albeit suboptimally. Despite differences in entry mechanisms and spike proteolytic activation compared to MERS-CoV, these viruses remain sensitive to several broadly neutralizing antibodies and entry inhibitors. These findings redefine our understanding of the evolution of receptor usage among MERSr-CoVs and highlight the versatility of ACE2 as a functional receptor for diverse coronaviruses. Significance Recent studies unexpectedly revealed that several merbecoviruses convergently evolved ACE2 receptor usage with distinct binding modes across three continents, challenging the dogma that DPP4 is their primary receptor. Here, we demonstrate that HKU25 clade MERS-related coronaviruses broadly distributed across Eurasia utilize ACE2 as host receptor through a binding mode shared with HKU5, challenging prior findings. These findings reveal a prevalence of ACE2 usage in diverse MERS-related coronaviruses in bats and show that EjCoV-3 is preadapted to use human ACE2, suggesting a potential for spillover. Our data provide a blueprint of host receptor barrier determinants which will facilitate global surveillance and development of countermeasures against these poorly characterized merbecoviruses.